The Continuum of Government and NGO Perceptions towards Socio-Cultural Dynamics in Ecotourism Development, Bopunjur, West Java - Widodo, Gatot; Avenzora, Ricky; Malihah, Elly; Sunarminto, Tutut (Universitas Negeri Semarang, 2023)
It cannot be denied that the government, which plays the role of policy maker, and NGOs, which act as policy controllers and supervisors, are an important and inseparable part of development because their orientation (perception, motivation and participation) greatly determine the success of ecotourism development. If previous research looked at their role partially, then in this study their role is analyzed in an integral and integrated manner which refers to the working principle of two human hands, the left hand and the right hand, which, if they work together, complement each other, thus resulting in optimal, qualified and sustainable ecotourism development. This study aims to analyze the continuumof government and NGO perceptions about socio-cultural dynamics in ecotourism development in the research area. This research was conducted in the area, Bogor Regency, West Java, in seven ecotourism destinations namely Ciawi, Caringin, Cibogo, Cipayung, Megamendung, Cisarua, and Tugu. This study uses an exploratory – phenomenology approach. Data collection on social and cultural dynamics was carried out by distributing closed questionnaires to the respondents. The research instrument was a closed ended questionnaire guided by a one score one scoring system indicator (Avenzora, 2008). The polarization of government and NGO perceptions of social values and cultural values is identified from two categories, namely the direction of polarization (polarization direction) and the polarization scale (polarization scale). The results of the study show that the socio-cultural dynamics of this ecotourism area have not fully led to the formation of optimal cultural carrying capacity due to the polarization of the orientation of government and NGO stakeholders on various aspects and assessment criteria. The polarization of stakeholder orientation regarding various socio-cultural aspects has a negative direction with polarization scales that are categorized as aligned so that there is a great opportunity to build productive collaboration between stakeholders in ecotourism development in the area.